2004
DOI: 10.1557/jmr.2004.19.1.301
|View full text |Cite
|
Sign up to set email alerts
|

Young's modulus measurements on ultra-thin coatings

Abstract: The determination of the mechanical properties of ultra-thin coatings has become more and more important because of the increasing number of applications using such films. However, an accurate mechanical testing of coatings with a thickness down to some nanometers is still a challenge, despite the improvements of existing measurement techniques. Nanoindentation is an often used mechanical nanoprobe. Using the conventional test method with a sharp Berkovich indenter, the problem of the influence of the substrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(38 citation statements)
references
References 20 publications
0
38
0
Order By: Relevance
“…Many fewer studies have been performed for the case of ceramics. However, it has been shown that diamond-like carbon thin films undergo a decrease in elastic modulus as their thickness decreases [92][93][94]. This decrease can be as much as 44% of the elastic modulus (360 GPa at 6 nm vs. 640 GPa at 125 nm thickness) [92].…”
Section: Stiffness Of Nanosized Hap Plateletsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many fewer studies have been performed for the case of ceramics. However, it has been shown that diamond-like carbon thin films undergo a decrease in elastic modulus as their thickness decreases [92][93][94]. This decrease can be as much as 44% of the elastic modulus (360 GPa at 6 nm vs. 640 GPa at 125 nm thickness) [92].…”
Section: Stiffness Of Nanosized Hap Plateletsmentioning
confidence: 99%
“…However, it has been shown that diamond-like carbon thin films undergo a decrease in elastic modulus as their thickness decreases [92][93][94]. This decrease can be as much as 44% of the elastic modulus (360 GPa at 6 nm vs. 640 GPa at 125 nm thickness) [92]. Using semi-continuum models on platelike nanomaterials a 27% decrease in the modulus for NaCl was predicted for thin films with less than 10 atomic layers [95].…”
Section: Stiffness Of Nanosized Hap Plateletsmentioning
confidence: 99%
“…It is generally accepted that for thin films on a substrate, if the indentation exceeds ∼10% of the film thickness, the measured hardness may be affected by the substrate properties [37]. No such rule has been applied for the Young's modulus; however several groups have tried to derive empirical formulas for effective modulus and compliance as a function of elastic properties of both materials [38][39][40][41]. Problems arise when testing the mechanical properties of the ZDDP tribofilms due to the fact that these films are extremely thin and may vary in thickness.…”
Section: Variable Temperature Nanoindentation Analysis Of the Tribofilmsmentioning
confidence: 99%
“…Because nanoindentation elastically deforms the sample at small strains, Poisson's ratio of the lens capsule was assumed to be 0.5. The Poisson's ratio and Young's modulus (n i and E i , respectively) of the sapphire flat punch indenter were obtained from Chudoba et al 23 By substituting these values into equation 2, 19 the Young's modulus from each indent was calculated.…”
Section: Nanoindentationmentioning
confidence: 99%